EnglishIntroduction and Training on Cosmetics with Natural Ingredients as an Effort to Enhance the Creativity of Al Azhar Students - Zulaicha, Annisaa Siti; Setiajaya, Arif (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
As a form of improving the quality of Indonesian education and also graduating Islamic-based high school students, Al Azhar High School has a mission, namely one of them is for Al Azhar High School students to become religious beings and also have abilities and skills that can be applied directly to society. Steps that can be taken are to provide skills to be able to make innovative products made from natural ingredients, one of which is a body scrub made from coffee grounds typical of Lampung Province. Cosmetic product innovation was chosen because today both at the national and world level the development of the use of cosmetics is increasing, of course this is a great opportunity to start entrepreneurship. In addition, the use of coffee grounds also supports the main results of Lampung plantations which have an area of coffee plantations of around 156,458 ha in 2020, in order to produce secondary products that have higher economic value. The purpose of community service is to provide introduction, education, and train Al Azhar Bandarlampung High School students to make coffee-based cosmetic products, namely Becoffee Body Scrub. The specific target is to make students become pioneers in increasing MSMEs in the field of cosmetics specifically in exploiting the Natural Potential of Sumatra, especially in Lampung province, into cosmetic products.